Recent Developments on the Earth-Abundant-Metal-Catalyzed α,β-Dehydrogenation of Carbonyl Compounds - Dai, Peng-Fei; Li, Qiang-Qiang; Qu, Jian-Ping; Kang, Yan-Biao (Synthesis, 2024)
α,β-Unsaturated carbonyl compounds are versatile building blocks in modern organic synthetic chemistry. In recent decades, various approaches have been established to access to these products, such as halogenation–dehydrohalogenation methods, organosulfur methods, organoselenium methods, earth-abundant-metal-catalyzed methods, precious-metal-catalyzed methods, and metal-free methods, etc. Among these, earth-abundant-metal-catalyzed methods (i.e., iron, cobalt, nickel, copper) continue to attract the attention of chemists because they are readily available, inexpensive, and environmentally friendly. Presently, there are only a few reviews covering earth-abundant-metal-catalyzed α,β-dehydrogenations. Hence, the aim of this short review is to provide a detailed update on the recent developments on earth-abundant-metal-catalyzed α,β-dehydrogenations of carbonyl compounds. 1 Introduction2 Iron-Catalyzed Dehydrogenation3 Cobalt-Catalyzed Dehydrogenation4 Nickel-Catalyzed Dehydrogenation5 Copper-Catalyzed Dehydrogenation6 Conclusion
Keywords: carbonyl compounds; earth-abundant metal; catalysis; α,β-dehydrogenation; α,β-unsaturated carbonyl compounds